2020
DOI: 10.3390/molecules25092146
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Milk Fat Globular Membrane (MFGM) Proteome between Saudi Arabia Camelus dromedary Safra and Wadha Breeds

Abstract: Camel milk is traditionally known to have medicinal properties and many potential health benefits. Natural milk contains many soluble proteins and nanoparticles, such as a milk fat globule membrane (MFGM), a three-layered membrane covering of milk fat globule mainly composed of proteins and lipids, which plays an important role in human health. MFGM proteins account for 1%–4% of total milk proteins, and their nutritive value and distribution depends on the different breeds. The differential composition of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The results showed that 6, 12 and 24 ng/µL camel milk exosomes significantly increased the glucose consumption of L6 cells for 24 h (P<0.05) (Fig 3). Camel milk can be used to treat diseases such as diabetes, cancer and gastrointestinal disease (Sabha et al 2020). Furthermore, camel milk exosomes have been shown to have anti-cancer effects by inhibiting inflammation and oxidative stress (Badawy et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that 6, 12 and 24 ng/µL camel milk exosomes significantly increased the glucose consumption of L6 cells for 24 h (P<0.05) (Fig 3). Camel milk can be used to treat diseases such as diabetes, cancer and gastrointestinal disease (Sabha et al 2020). Furthermore, camel milk exosomes have been shown to have anti-cancer effects by inhibiting inflammation and oxidative stress (Badawy et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, increasing attention has been paid to the components of MFGM, especially to their protein components [ 47 ]. MFGM proteins, which account for 1–4% of the total milk protein, differ depending on the breed [ 48 ]. The proteins of camel MFGM are mainly involved in protein processing, bio-synthesis of fat, and actin cytoskeleton organization [ 47 , 49 ].…”
Section: Composition and Functional Properties Of CM Fat Globule And Membranementioning
confidence: 99%
“…During the secretion of the MFGs [ 50 ], the localization of the proteins differs: some are related to the inner monolayer membrane, while others to the outer bilayer membrane [ 51 , 52 ]. Camel MFGM proteins have been investigated in order to explain MFGM structure and how the proteins vary between the different species [ 47 , 48 , 49 ].…”
Section: Composition and Functional Properties Of CM Fat Globule And Membranementioning
confidence: 99%
See 1 more Smart Citation
“…The expression of all these endogenous bioactive peptides in raw camel milk would might explained our previous results [ 3 ], where the consumption of raw camel milk (from Camelus dromedary ) for three months (250 ml/day) by patients infected with hepatitis C virus, at different disease stages, promoted a significance reduction in the viral load, as well as improved the general health fitness biomarkers, may be due to the existence of the arrays of bioactive peptides with the potential to regulate and control various cellular pathways. The significance differences in both qualitative and quantitative levels of endogenous peptides are not restricted to the differences in the Dromedary and Bactrian camel milk [ 1 ], but it is also found between the intraspecies “breeds” of the Dromedary [ 4 ]. Recently, the purified and/or formulated samples of lactoferrin (which may contain some of the endogenous bioactive peptides) was used for COVID-19 control [ 5 ].…”
mentioning
confidence: 99%